A case study of pillar extraction techniques based on strip-filling and second-mining method - Hao, Jian; Chen, Anfa; Li, Xuelong; Bian, Hua; Shi, Yongkui; Wang, Xin; Zhao, Jiali; Liu, Haojie (Frontiers in Earth Science, 2022)
Strip coal pillars caused by strip mining are widely distributed in China. Over time, strip coal pillars are posing more potential hazards as their stability decreases; therefore, it becomes increasingly important to recover coal pillars without damaging the ground surface. In this paper, strip-filling and second-mining technique is adopted to probe into an optimal scheme for mine goafs. Construction waste was one type of the materials used for backfilling, which was taken to underground from the surface with a pumping system. Jisuo Coal Mine of Tengzhou, Shandong province was taken as the object of study. Through theoretical calculation and on-site survey, we set a re-mining scheme to control rock stratum stability, i.e., 8-meter-wide backfilling for the first time and 4-meter-wide backfilling for the second time; moreover, the ground pressure behavior and subsidence of working surface were monitored and a contour map of surface subsidence was thus mapped. In-situ practice indicated that the underground pressure from coal pillars was transmitted to the backfilling materials, the maximum normal stress of which was 5 MPa, so it was sufficient for the backfilling strip to support the weight of overlying strata; the maximum value of roof-to-floor convergence of backfilled mining face is 45 mm, the maximum surface subsidence 44mm, the maximum inclination value 0.65 mm/m, the maximum surface curvature 0.018 mm/m2, and the maximum horizontal deformation 0.16 mm/m. The filling body in the original goafs plays the role of "pier". By the monitoring data of subsidence, its surface deformation value was less than that of buildings suffering from grade I damage, which verified the feasibility of strip-filling and second-mining scheme. The success in this technique provides reliable technical and theoretical support for mines with similar conditions.